IDENTIFIKASI EVENT BUDAYA SEBAGAI ATRAKSI WISATA DI DESA MEAT – SUMATERA UTARA - Nukeu Novia Andriani; Aji Prasetya Hadi; Yuwana Marjuka (Sekolah Tinggi Pariwisata Mataram, 2023)
This research is to find out opportunities for tourist attractions and develop tourism villages through cultural events in Meat Tourism Village. This research uses qualitative methods with a Grounded Theory approach. Data collection is done through observation techniques or field surveys, interviews, documentation. The research results obtained are that Meat village has a tourist attraction, divided into 3 namely natural, cultural, and special interest tourist attractions such as tourism events. This research is expected to contribute to the development of tourism research in tourist villages in the development of tourist attractions based on festival events